Getting started with Windows 8 - Halsey, Mike (O'Reilly Media, 2013)
"In this webcast, Mike Halsey MVP, the author of "Windows 8: Out of the Box" will introduce the new Metro interface in Windows 8, show you how to use it and get the best out of it, and help build your confidence with your new computer."--Resource description page.